(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, in the poems of the folk poet of Uzbekistan Usman Azim, written on the basis of folk tales, the unique aspects of the poet’s creativity, the most common images in folk tales, and the situations of the plot line are highlighted as examples from several poems of the creator. given The poem "Alpomish", which reflects the deepest roots of the poet’s work, and their unique interpretation are discussed.